Perancangan dan Pengembangan Lembar Kerja Interaktif Materi Aritmetika Sosial untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - Adji W. S. Minadja; Sugeng Sutiarso; Rangga Firdaus; Kenny Candra Pradana; Karsoni Berta Dinata (Mandalika Mathematics and Educations Journal, 2025)
Design interactive worksheets based on Canva and Liveworksheets is the aim of this project to assist students in developing their social arithmetic problem-solving abilities. The research methodology employed was research and development (R&D) using the ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation. The participants were seventh-grade students and a math teacher from SMP Negeri 5 Kotabumi, Lampung. Tests of problem solving skills, observations, interviews, and questionnaires were employed to gather both qualitative and quantitative data. Subject matter experts' validation assessment, which received a score of 0.84 (very valid), media experts' score of 0.90 (valid), and students' and instructors' practicality index scores of 0.80 (practical) and 0.90 (very practical) all demonstrate the study's findings. The effectiveness of the interactive worksheet developed can be seen based on the testing of the n-gain data hypothesis listed in the significance section (2-tailed), which is 0.0017. There is a difference in the improvement of problem solving skills for students who use interactive worksheets. The novelty of this research lies in the development of interactive worksheets based on the Canva and Liveworksheet digital platforms, which integrate visualization, direct interaction, and automatic feedback to improve students' problem solving skills in social arithmetic. Thus, these findings show that the worksheets are valid, practical, and effective in improving students' problem solving skills.